Isolation, purification and partial characterization of bioactive fractions from Chaetoceros calcitrans - Ticar, Bernadeth Figueroa (University of the Philippines Visayas, 2008)
Phytochemical screening results on the crude methanolic extract of the microalga, Chaetoceros calcitrans showed the presence of a flavonoid compound. The solvent extracts of C. calcitrans (Methanoll, n-Hexanne, Dichloromethane and Ethyl acetate) were subjected to antibacterial assay against S. Aureus, B. subtilis, E. Coli and v. Results showed that all fractions have antibacterial activities towards all the test organisms with n-hexane fraction having a relatively wider spectrum of activity among the solvent fractions. This was subjected .to Vacuum Liquid Chromatography followed by Thin-Layer Chromatography. The TLC results indicated the probable presence of terpenes and the results indicated that the component was found in the nonpolar fraction (C2). The Fourier Transfrom-Infrared (FT-IR) spectroscopy was used to partially characterize the C2 fraction. The spectra showed that thecompound is aliphatic due to the C-H stretching at 2860.84cm-1 and bending vibrations at 1462.61cm-1 and 1380.75 cm-1. A C=0 signal was detected at 1728.56 cm-1 and an O-H group at 3424.94 cm-1. The unsaturation of the compound can be supported by the signal at 2928.16cm-1 and a vinylidene group at 1122.58 cm-1 and 1280.84cm-1. The results of this study may indicate the probable presence of a flavonoid or a terpenoid compound on Chaetoceroscalcitrans.